2018
DOI: 10.1002/cphc.201800466
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Substituted Coronene: Intriguing Geometric and Electronic Properties, and Large Nonlinear Optical Response

Abstract: By substituting boron atoms for selected carbon atoms of a graphene quantum dot (GQD) model, namely a coronene molecule, the substituent effect on its geometric and electronic structure, as well as nonlinear optical response has been systemically investigated in theory. Our computations reveal that the boron substitution leads to a similar noncentrosymmetric apophysis structure for the boron-substituted coronene in singlet and triplet states. Noticeably, due to the small energy difference of 2.5 kcal mol betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…27 In another similar study, the reported b o of lithium doped cyclic conjugated ring system was 7.3 Â 10 3 au 33 and 3 Â 10 4 au. 34 In this study, we found that the NLO responses of alkali and superalkalis doped 6CT complexes have shown good agreement with the previously reported similar systems. 35,36 Two level model is performed to interpret the effects of change in dipole moment (Dm), oscillator strength (f o ) and crucial excited Fig.…”
Section: Static Nlo Responsessupporting
confidence: 89%
See 2 more Smart Citations
“…27 In another similar study, the reported b o of lithium doped cyclic conjugated ring system was 7.3 Â 10 3 au 33 and 3 Â 10 4 au. 34 In this study, we found that the NLO responses of alkali and superalkalis doped 6CT complexes have shown good agreement with the previously reported similar systems. 35,36 Two level model is performed to interpret the effects of change in dipole moment (Dm), oscillator strength (f o ) and crucial excited Fig.…”
Section: Static Nlo Responsessupporting
confidence: 89%
“…It is postulated that NLO active material should be transparent in the interested region of EMR spectrum. 34 In order to find the adsorption wavelength of 6CT before and after doping, the UV-vis analysis is performed at TD/M05-2X/6-31+G(d,p). It is cleared from the results ( Table 3 & Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene (G) has a symmetric six-membered ring center and, hence, its second hyperpolarizability is quite small. The substitution of heteroatom such as boron on this central ring, however, enhances the first hyperpolarizability remarkably . Further, it was reported that the second hyperpolarizability of hexalithiobenzene (C 6 Li 6 ) is significantly large .…”
Section: Introductionmentioning
confidence: 98%
“…The substitution of heteroatom such as boron on this central ring, however, enhances the first hyperpolarizability remarkably. 25 Further, it was reported that the second hyperpolarizability of hexalithiobenzene (C 6 Li 6 ) is significantly large. 26 To increase the first hyperpolarizability, we recently studied the complexes of C 6 Li 6 with an alkali atom (M) and noticed a remarkable increase in the first static hyperpolarizability for M = Li, Na, and K. 27 This motivated us to perform an in-depth study on lithiated graphene (LiG) and investigate the effect of a single alkali atom.…”
Section: Introductionmentioning
confidence: 99%